2022
DOI: 10.3390/molecules27217415
|View full text |Cite
|
Sign up to set email alerts
|

Labeling Microplastics with Fluorescent Dyes for Detection, Recovery, and Degradation Experiments

Abstract: Staining microplastics (MPs) for fluorescence detection has been widely applied in MP analyses. However, there is a lack of standardized staining procedures and conditions, with different researchers using different dye concentrations, solvents, incubation times, and staining temperatures. Moreover, with the limited types and morphologies of commercially available MPs, a simple and optimized approach to making fluorescent MPs is needed. In this study, 4 different textile dyes, along with Nile red dye for compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…72 The dyeing method is typically used to facilitate frequent identification of MPs. Based on previous reports, Rose Bengal, 73 Nile red, 74 Eosin B, 75 and Oil Red EGN 76 were used as dyes in this method (Figure 4). Among these, Nile red dye provided the best results.…”
Section: Methodology For Liquid Foodmentioning
confidence: 99%
“…72 The dyeing method is typically used to facilitate frequent identification of MPs. Based on previous reports, Rose Bengal, 73 Nile red, 74 Eosin B, 75 and Oil Red EGN 76 were used as dyes in this method (Figure 4). Among these, Nile red dye provided the best results.…”
Section: Methodology For Liquid Foodmentioning
confidence: 99%
“…Nevertheless, some polymer types can be sensitive to high temperatures [29][30][31]. Other studies have also revealed that higher temperatures have a positive impact on the staining procedure [25][26][27][28]. Higher temperatures can yield a better adsorption of the fluorescent dye onto the MP surface and into the polymeric network.…”
Section: Staining Temperaturementioning
confidence: 99%
“…7,8 Fluorescence microscopy (FM) combines the magnication capabilities of an optical microscope with the uorescence emission properties of dyed compounds to generate a magni-ed, uorescent image. 9 FM provides information on size, shape, and morphology, and it can also be used to count and determine the concentration of MPs. Also, scanning electron microscopy (SEM) uses an electron beam instead of visible light to scan the surface of an object to create a high-resolution, magnied image, but it is costly and requires much training to use.…”
Section: Introductionmentioning
confidence: 99%